Identifying Hate Speech on Israeli Netizent Tiktok - Wulan Sari Silalahi; Arsen Nahum Pasaribu; Rotua Elfrida Pangaribuan (Journal of Language Education (JoLE), 2025)
The purpose of this study are to find out the impoliteness strategy of hate speech netizens use on TikTok accounts against the state of Israel and to find out the dominant types of impoliteness strategies of hate speech netizens use on TikTok accounts against the state of Israel. This study used the descriptive-qualitative method. In the results of the data analysis, the writer found four types of impoliteness strategies in comments on Israeli state accounts, namely Bald on on-record impoliteness. There are 14 (12%) comments of positive impoliteness, 8 (8%) comments of negative impoliteness, 59 (59%) comments of sarcasm, politeness, 19 (19%) comments of withhold politeness, and 0 (0%) comments. The writer finds that the most dominant type of strategy used is the impoliteness strategy or negative impoliteness. This type is more frequently used because of the high emotional dissatisfaction shown by the speaker against Israel. Sensitive topics such as political conflicts or controversial international situations often provoke strong emotions and discontent among social media users. Netizens believe that Israel violates human rights or treats certain groups unfairly, especially in the context of the Israeli-Palestinian conflict. This can cause a negative reaction, and some social media users may use negative disobedience to show support or solidarity to groups or parties involved in conflict with Israel.